2004
DOI: 10.1080/08830180490265538
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell and Neuronal Apoptosis in Hiv Infection: Implications for Therapeutic Intervention

Abstract: The pathogenesis of HIV infection involves the selective loss of CD4+ T cells contributing to immune deficiency. Although loss of T cells leading to immune dysfunction in HIV infection is mediated in part by viral infection, there is a much larger effect on noninfected T cells undergoing apoptosis in response to activation stimuli. In the subset of patients with HIV dementia complex, neuronal injury, loss, and apoptosis are observed. Viral proteins, gp120 and Tat, exhibit proapoptotic activities when applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 245 publications
0
20
1
Order By: Relevance
“…Taken together, our investigation and previous reports suggest that therapeutic strategies to reduce the level of inflammation and increase mucosal growth and injury repair should be investigated to enhance the efficacy of anti-HIV or -SIV therapy in restoring mucosal immune system. Down regulation of lymphocyte activation during HIV infection has been proposed by several investigators as a potential method to improve the rate of disease progression (3,5,17,24). It is also noteworthy that inhibitors of tumor necrosis factor have been shown to markedly reduce mucosal inflammation caused by infection of intestinal xenografts, suggesting that tumor necrosis factor-associated pathways may play an important role in the manifestation of intestinal inflammation in HIV and SIV infections (43).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our investigation and previous reports suggest that therapeutic strategies to reduce the level of inflammation and increase mucosal growth and injury repair should be investigated to enhance the efficacy of anti-HIV or -SIV therapy in restoring mucosal immune system. Down regulation of lymphocyte activation during HIV infection has been proposed by several investigators as a potential method to improve the rate of disease progression (3,5,17,24). It is also noteworthy that inhibitors of tumor necrosis factor have been shown to markedly reduce mucosal inflammation caused by infection of intestinal xenografts, suggesting that tumor necrosis factor-associated pathways may play an important role in the manifestation of intestinal inflammation in HIV and SIV infections (43).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Regulier et al 32 and Luker and Leib 33 demonstrated that Tat exerts a negative effect on cell growth in neural cells in CNS, while Bettaccini et al 34 has noted mitogenic effects on mammary and amniotic epithelial cells. We found out that HIV-1 Tat protein was able to speed up proliferation of HeLa cells through increase in cyclin A expression and downregulation of CKIs.…”
Section: Hiv-1 Tat Oncogenic Role In Cervical Carcinogenesismentioning
confidence: 99%
“…The mechanisms of apoptosis in T cells and neurons appear to be similar, involving death receptors (TNF receptors and Fas), some chemokines, calcium dysregulation, mitochondrial membrane permeabilization and caspase activation. 123 Both gp120 and Tat may be key triggers of apoptosis in different cell types that die in HIV-1 AIDS. HIV-1-infected monocytes produce a protein called FLJ21908 that is cytotoxic to CD4( þ ) and CD8( þ ) T and B cells, as well as in neuroblastoma cells.…”
Section: Apoptosismentioning
confidence: 99%